Transcriptome Modifications in the Porcine Intramuscular Adipocytes during Differentiation and Exogenous Stimulation with TNF-α and Serotonin - Tada, Asuka (2020)
Adipocytes are dynamic cells that have critical functions to maintain body energy homeostasis. Adipocyte physiology is affected by the adipogenic differentiation, cell program, as well as by the exogenous stimulation of biochemical factors, such as serotonin and TNF-α. In this work, we investigated the global transcriptome modifications when porcine intramuscular preadipocyte (PIP) was differentiated into porcine mature adipocyte (pMA). Moreover, we studied transcriptome changes in pMA after stimulation with serotonin or TNF-α by using a microarray approach. Transcriptome analysis revealed that the expression of 270, 261, and 249 genes were modified after differentiation, or after serotonin and TNF-α stimulation, respectively. Expression changes in APP, HNF4A, ESR1, EGR1, SRC, HNF1A, FN1, ALB, STAT3, CBL, CEBPB, AR, FOS, CFTR, PAN2, PTPN6, VDR, PPARG, STAT5A and NCOA3 genes which are enriched in the ‘PPAR signaling’ and ‘insulin resistance’ pathways were found in adipocytes during the differentiation process. Dose-dependent serotonin stimulation resulted in a decreased fat accumulation in pMAs. Serotonin-induced differentially expressed genes in pMAs were found to be involved in the significant enrichment of ′GPCR ligand-binding′, ‘cell chemotaxis’, ‘blood coagulation and complement’, ‘metabolism of lipid and lipoproteins’, ‘regulation of lipid metabolism by PPARA’, and ‘lipid digestion, mobilization and transport’ pathways. TNF-α stimulation also resulted in transcriptome modifications linked with proinflammatory responses in the pMA of intramuscular origin. Our results provide a landscape of transcriptome modifications and their linked-biological pathways in response to adipogenesis, and exogenous stimulation of serotonin- and TNF-α to the pMA of intramuscular origin.